Differential Association of Free, Conjugated, and Bound Forms of Polyamines and Transcript Abundance of Their Biosynthetic and Catabolic Genes During Drought/Salinity Stress in Tomato (Solanum lycopersicum L.) Leaves - Upadhyay, Rakesh K.; Fatima, Tahira; Handa, Avtar K.; Mattoo, Autar K. (Frontiers in Plant Science, 2021)
Polyamines (PAs) have been implicated in ameliorating detrimental effects of drought and saline conditions on plant growth and development. The independent impact of these two abiotic stresses on polyamine biosynthesis, catabolism and homeostasis as well as on their transcript abundance in tomato leaves is presented here. We show that the total levels of putrescine (PUT), spermidine (SPD) and spermine (SPM) increase up to 72 h during drought and up to 48 h during salinity stress before their precipitable drop thereafter. Thus, tomato plants maintain survivability to drought as well as salinity stress for up to 3 d and 2 d, respectively. Independent multivariant analyses of drought and salinity stress kinetic data separately showed closer association with levels of free, conjugated and bound forms of SPD and SPM, but not with free or bound PUT. However, combined multivariant analyses showed closer association of free SPD, conjugated SPD and bound SPD with both stresses, SPD-bound and SPM-conjugated with drought, and free SPM and conjugated PUT with salinity stress, respectively. PA biosynthesis genes, ARG1, SPDS1 and SAMDc3, segregated with drought and SPDS2 with salinity stress. PA catabolic genes CuAO4-like and PAO4 were associated with drought and salinity stresses, respectively, suggesting differential involvement of PA biosynthesis and catabolic genes in drought and salinity stresses. Pearson correlation indicated mostly positive correlations between the levels of free, conjugated and bound forms of PUT, SPD and SPM under drought and salinity stress. However, negative correlations were mostly seen between the levels of various forms of the PAs and their biosynthesis/catabolic genes. Levels of different PA forms had 2-fold higher negative correlation during drought as compared to salinity stress (66 vs 32) and with transcript levels of PA biosynthesis and catabolic genes. Transcripts of light-harvesting chlorophyll a/b-binding genes were generally positively associated with different forms of PAs but negatively to carbon flow genes. PA biosynthesis genes were coordinately regulated under both stresses. Collectively, these results indicate that PAs are distinctly regulated under drought and salinity stress with different but specific homologues of PA biosynthesis and catabolic genes contributing to accumulation of free, conjugated and bound forms of PAs.